Clinical Evaluation of Blood Pressure Lowering, Endothelial Function Improving, Hypolipidemic and Anti-Inflammatory Effects of Pomegranate Juice in Hypertensive Subjects - Asgary, Sedigheh; Sahebkar, Amirhossein; Afshani, Mohammad Reza; Keshvari, Mahtab; Haghjooyjavanmard, Shaghayegh; Rafieian-Kopaei, Mahmoud (Phytotherapy research, 2014)
Pomegranate (Punica granatum L.) juice (PJ) contains different types of antioxidants and bioactive polyphenols and has been reported to promote cardiovascular health through several mechanisms. The present study aimed to examine the effects of 2‐week intake of fresh PJ on blood pressure, flow‐mediated dilatation (FMD), serum lipid profile and concentrations of inflammatory and endothelial function biomarkers. Twenty‐one hypertensive patients (aged 30–67 years) were recruited into the trial and assigned to receive either PJ (150 ml/day in a single occasion between lunch and dinner; n = 11) or the same amount of water (n = 10) for a period of 2 weeks. Systolic (SBP) and diastolic (DBP) pressures together with FMD and serum concentrations of lipid profile parameters, apolipoproteins A and B, intracellular adhesion molecule‐1 (ICAM‐1), vascular endothelial adhesion molecule 1 (VCAM‐1), E‐selectin, high‐sensitivity C‐reactive protein (hs‐CRP) and interleukin‐6 (IL‐6) were measured at baseline and at the end of trial. PJ consumption was associated with significant reductions in SBP (p = 0.002) and DBP (p = 0.038) but not FMD (p > 0.05). Serum levels of VCAM‐1 (p = 0.008) were significantly reduced by PJ while those of E‐selectin were elevated (p = 0.039). However, no significant effect was observed from PJ on serum levels of ICAM‐1, hs‐CRP, lipid profile parameters, apolipoproteins and IL‐6 in any of the study groups (p > 0.05). Consumption of PJ for 2 weeks has effective hypotensive effects, and may improve endothelial function by decreasing serum concentrations of VCAM‐1. These findings suggest PJ as a beneficial cardioprotective supplement for hypertensive subjects. Copyright © 2013 John Wiley & Sons, Ltd.